Cost benefit of different anthelmintic dosages in relation to weight gain of beef calves - Lima, Walter dos Santos; Guimarães, Marcos Pezzi; Leite, Antonio Cesar Rios (Pesquisa Agropecuaria Brasileira, 2014)
Four groups of ten beef calves each received different numbers of anthelmintic treatments for one year as follows: Group A - one treatment; Group B - Two treatments; Group C - Three treatments and Group D - control. The cost benefit of these treatments was calculated, and Group A had a performance 1.55%, Group B 5.40% and Group C 21. 49% better than Group D.